Can't You All Just Get Along? Effects of Scientific Disagreement and Incivility on Attention to and Trust in Science. Issue 1 (February 2022) - Chinn, Sedona; Hart, P. Sol
Disagreement and incivility are increasingly common in science communication. While previous work has explored effects on issue attitudes, it has not examined how disagreement and incivility in news coverage influence attention to and trust in science. In this study, we investigate how civil and uncivil disagreement about non-politicized issues affects attention to science news, evaluations of research, and scientific trust. Results reveal that disagreement and incivility can not only lead to less attention to and acceptance of particular science issues, but also broader mistrust of scientists and scientific methods.